2020
DOI: 10.15244/pjoes/115327
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hydrogen Peroxide Against Cucumber Green Mottle Mosaic Virus Infection in Watermelon Plants

Abstract: The aim of this work was to study the effects of hydrogen peroxide (H 2 O 2) application against cucumber green mottle mosaic virus (CGMMV) infection in watermelon (Citrullus lanatus) plants. From the obtained results, the induced resistance using H 2 O 2 treatments caused a delay in the appearance of CGMMV symptoms in watermelon plants. The viral infection showed abnormal morphological symptoms such as mosaics, yellow blisters and reduction in size. Pretreatment with H 2 O 2 before infection was beneficial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…for MDA and H 2 O 2 , respectively) ( Figure 6 ). These results are consistent with those found in many other studies of viral infections in plants [ 56 , 57 , 58 , 59 , 60 ]. The increase in the level of oxidative stress markers in plant cells that are infected is thought to be a defense mechanism against infection.…”
Section: Resultssupporting
confidence: 93%
“…for MDA and H 2 O 2 , respectively) ( Figure 6 ). These results are consistent with those found in many other studies of viral infections in plants [ 56 , 57 , 58 , 59 , 60 ]. The increase in the level of oxidative stress markers in plant cells that are infected is thought to be a defense mechanism against infection.…”
Section: Resultssupporting
confidence: 93%
“…Hydrogen peroxide is also one of the chemical inducers of SAR, which in turn signals the activation of defence genes and the formation of phytoalexins (Hernández et al., 2016; Kuźniak & Urbanek, 2000; Liao et al., 2013; Orozco‐Cardenas & Ryan, 1999). It has been reported that H 2 O 2 plays a signalling role in plants under stress and pathogen defence, particularly against virus infection (Radwan & Ismail, 2020). In the current study, treatment of stem cuttings with 1% H 2 O 2 eliminated EACMV and ACMV in more than 77.8% of the sprouted plants.…”
Section: Discussionmentioning
confidence: 99%
“…(2019), where exogenous application of H 2 O 2 protected pepper plants from pepper golden mosaic virus. Radwan and Ismail (2020) found that exogenous application of H 2 O 2 in watermelon plants protected the plants from cucumber green mottle mosaic virus infection, demonstrating the useful application of H 2 O 2 in a range of plant–virus systems. However, the use of a higher concentration of H 2 O 2 in the current study and exposure time compromised the survival and growth of plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies also reported the effects of infection with various diseases on antioxidant enzyme activities. The Cucumber Green Mottle Mosaic Virus infection induced higher APX, POX, and SOD activities in cucumber plants [ 84 ]. The results of Kovács et al [ 85 ] showed higher APX, POX, and SOD activities in European chestnut leaves infected with Cryphonectria parasitica .…”
Section: Discussionmentioning
confidence: 99%